The Development of Academic Vocabulary in International Foundation Students’ Assessed Academic Writing - Therova, Dana (Journal of International Students, 2021)
Despite the extensive research into academic vocabulary in university student writing, little is known about academic vocabulary in international foundationlevel students’ assessed academic writing. Considering that academic vocabulary is regarded as a key element of academic writing style and that written assignment is one of the main forms of assessment in university contexts, this is an important omission. This study addresses the gap by employing a corpus-based approach to investigate the development of academic vocabulary in assessed academic writing produced by international students (N = 193) in a foundation (gateway) program over an academic year in the context of a British university based in England and its overseas campuses in the United Arab Emirates and Mauritius. The findings show an increase in the usage of academic vocabulary over the course of the foundation program and highlight the impact of the assignment topic and brief.